Point‐of‐care measurement of fetal blood lactate – Time to trust a new device. (31st July 2017) - Wang, Mandy; Chua, Seng C.; Bouhadir, Lilain; Treadwell, Erin L.; Gibbs, Emma; McGee, Therese M.
Abstract : Background: Point‐of‐care lactate devices are used worldwide for intrapartum decision making. Current practice is often based on Lactate Pro (Arkray) but its imminent product discontinuation necessitates determination of an optimal replacement device. Aims: To evaluate the performance of Lactate Pro and two other point‐of‐care devices, Lactate Pro 2 (Arkray) and StatStrip (Nova Biomedical), and to derive scalp lactate cut‐offs equivalent to the current intervention trigger of >4.8 mmol/L. Materials and methods: Paired umbilical cord arterial and venous blood samples from 109 births were tested on the three point‐of‐care products (two devices each), cross‐compared with the reference method blood gas analyser. Results: All brands deviate from the blood gas analyser, with Lactate Pro and StatStrip results consistently lower and Lactate Pro 2 consistently higher. Standard deviation from the blood gas analyser was smallest for StatStrip (0.78 mmol/L, cord artery), and largest for Lactate Pro 2 (1.03 mmol/L, cord artery). Within‐brand variation exists and is similar for all brands (mean absolute difference on cord artery 0.23–0.30 mmol/L). Equivalent values to the 4.8 mmol/L intervention threshold based on Lactate Pro are 4.9–5.0 mmol/L for StatStrip and 5.3–5.9 mmol/L for Lactate Pro 2, calculated by receiver‐operating characteristic analysis. Conclusions: StatStrip appears superior to Lactate Pro 2 to replace the original Lactate Pro. Using StatStrip, the 4.8 mmol/L intervention threshold equivalent was 4.9–5.0 mmol/L. The variation in accuracy of point‐of‐care lactate devices may exceed the small increments (eg <4.2 mmol/L vs >4.8 mmol/L) that guide obstetric decisions.